Elements Shaping the South African Education System of the Future - Barends, Heidi (2019)
The South African education system is deeply unjust because a child’s place of birth, skin colour and family’s income largely determines their educational attainment. Understanding future trends and developments can assist stakeholders in planning and decision making. Better decisions could ultimately improve the education system. Therefore, this research aims to answer three questions: What trends could impact the South African education system? What opportunities and threats arise due to these trends? Who could influence the system?  To address these questions, a mixed-method approach was adopted. First, conceptual systems diagrams were developed to depict the current education system and its stakeholders. Then, semi-structured expert interviews were used to identify future trends, threats and opportunities.  This study found that the trends impacting South Africa broadly align with global trends. Examples include an increase in privatisation, technology in schools and climate change. More violence in schools is the main outlier. The study found that the risks related to technology and climate change are not being planned or accounted for. Similarly, violence is currently not a priority. The study also found that participants agreed on who the major stakeholders are, but disagreed on what actions stakeholders should take.
Keywords: Actor Diagram; Basic Education; CLD; Causal Loop Diagram; Education System; Foresight Study; Future Study; Future Trends; South African Education System; Systems Approach; _C:China CHN; _C:Germany DEU; _C:India IND; _C:Japan JPN; _C:Nigeria NGA; _C:Pakistan PAK; _C:South Africa ZAF; _C:Turkey TUR; _C:United Kingdom GBR; _C:United States USA; __C:scheme:1; _not_EdTechHub; _zenodoOTHER

School factors related to the emotional wellbeing and resettlement outcomes of students from refugee backgrounds: Protocol for a systematic review - Horswood, Deserae; Baker, Jess; Fazel, Mina; Rees, Susan; Heslop, Linda; Silove, Derrick (Systematic Reviews, 2019)
Background: Schools can play a vital role in the resettlement of refugee children and their families. Yet, the body of research examining school environmental factors that support the mental health and acculturation of refugee children is methodologically heterogeneous, investigates numerous and disparate school factors, and is often "hidden" in broader qualitative studies. This limits the capacity to apply the findings in a practical manner. Methods: Based on PRISMA statement principles, we review the relevant literature to investigate the relationship between school climate and the emotional wellbeing and resettlement outcomes of refugee students. Six electronic databases will be systematically searched: MEDLINE, PsycINFO, Embase, CINAL, Web of Science, and ERIC, supplemented by a systematic review of the grey literature, relevant international websites, and sequential, site-specific internet searches. Finally, subject area experts will be consulted and backward and forward citation searches of included articles will be completed. Two independent reviewers will screen identified articles against eligibility criteria and extract data for included studies. Quality of included studies will be assessed using the Mixed Methods Appraisal Tool (MMAT) for mixed studies reviews. Data will be synthesised using a convergent qualitative narrative approach. Discussion: Given the centrality of school in the daily lives of resettled refugee children, it is vital to assess the impact of school climate on the psychosocial wellbeing and resettlement trajectories of this population. This review will identify evidence-based school factors which support good mental health and resettlement outcomes for refugee students and make recommendations for translation of this knowledge into the school environment.
Keywords: Acculturation; Mental health; Refugee; Resettlement; School; Systematic review

Hello, I’m Björn, Director of Research – The EdTech Hub - Haßler, Björn (EdTech Hub, 2019)
I’m Dr Björn Haßler, one of the three Directors of Research for the programme. Research, and particularly at-scale research, is a core focus for the #EdTechHub and that’s why we have three Directors of Research, who will also introduce themselves. I am — we all are — extremely happy that we have been awarded the programme. We, like all our competitors, worked hard for around 1.5 years until the final submission. However, this work paid off! It means we can get going on the important mission.
Keywords: _DOILIVE; _EdTechHub_Output; _yl:r; _zenodoODE; dode_eth-src-eth; dode_eth-trf2-dode

Sustaining learner participation and progression through networked schooling: a systemic approach for Mobile Out of School Children - Dyer, C.; Echessa, E. (International Journal of Educational Development, 2019)
Despite repeated calls for education systems to respond flexibly to enable all children to participate in formal education, limited progress has been made for those we term Mobile Out of School Children (MOOSCs). Livelihood-related mobility often precipitates a process of learner drop out during the year. Retention of such children, and reducing the risk of their relapsing into MOOSC status, requires a re-framing of ‘school’ as a spatially dispersed system, or network, to accommodate learner movement. Networked schooling for children in mobile pastoralist communities in Ethiopia embeds formal education within mobile pastoralists’ resource management practices and orientates service provision accordingly. Although it is resource-intensive, networked schooling enables the requisite flexibility to support retention of pastoralist and other mobile learners. It of significant interest to global effort towards leaving none behind, particularly in the global drylands and other contexts where climate change is making learner mobility increasingly complex, and the need for a systemic response ever more pressing.